Complete conditioning for volleyball - Oldenburg, S. (Human Kinetics, 2015)
Get in top volleyball shape by using the same training techniques as the powerhouse UCLA teams use! Complete Conditioning for Volleyball—written by the Bruins` legendary coach, Al Scates, and St. Louis University`s strength and conditioning coordinator, Mike Linn—will have you serving with more power and consistency, skying higher on every jump, and covering the court with increased quickness and agility. Utilizing this winning training program has direct on-court results, as your digs, kills, and blocks increase and you remain strong through the end of every match. The perfect workout manual for coaches and players alike, Complete Conditioning for Volleyball links the drills and exercises to diagrams and photos in easy-to-understand fashion. The latest title in the popular Complete Conditioning for Sports series, this book follows a formula proven to get athletes in the best possible shape for their sport. You`ll find beneficial, volleyball-specific exercises and drills for in-season and off-season, on-court and off-court practice. Over the past four decades, Coach Scates has set the standard for success in collegiate volleyball, netting 18 NCAA Division I championships. With his book Complete Conditioning for Volleyball, he gives you the perfect set for you to score with greater fitness on the court.